(untitled) (Italian Journal of Public Health, 2007)
Professor Egon Diczfalusy reflects on a lifetime of experience, drawing insights from not only the great masters of the arts, philosophy and the sciences but also from a time in history in which he has witnessed some of the greatest triumphs in science as well as some of the greatest tragedies against humanity. This paper highlights some of the most pressing public health issues facing the world today, such as population growth and the changing global population structure, examining factors such as longevity and the progressive imbalance between the number of elderly persons in our communities and the number of persons who are able to support them. Finally he discusses the falling rates in fertility, stressing its multifactorial aetiology. In his closing remarks he poses three major problems that face the scientific community today. The use and misuse of science The growing discrepancy between scientific development and our moral/ethical development. The need to convince todays and future generations that fanatic faith, fundamentalism and obscurantism will not improve the quality of life of their children and grandchildren. His final reflections remind us that we belong to a humanistic science one in which we should not only strive to achieve the wisdom of humility but also the wisdom of hope.